PROCESS PARAMETER OPTIMIZATION IN LATHE TURNING OPERATION TO IMPROVE THE SURFACE ROUGHNESS AND REDUCE THE CUTTING FORCE USING TAGUCHI METHOD - SUBHABRATA BANERJEE,; SUMON KUNDU,; SUPRATIM CHOUDHURY, (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper represents an experimental study of Process Parameter Optimization to Improve the Surface Roughness generated and Reduction of the Cutting Force used in Lathe Turning Operation on a mild steel job and optimization of machine parameters by Taguchi Method. The Surface Roughness Parameter is the Response Surface Methodology. For developing mathematical model for predicting surface roughness parameter and cutting forces, the threelevel central composite design is employed.Taguchi method is a statistical approach in optimizing the process parameters used in quality control process to improve the quality of the manufactured component. In the following analysis three parameters namely speed, feed and depth of cut were considered. Experiment was conducted considering a suitable orthogonal array. Cutting force and surface roughness were measured and Signal to Noise ratio was calculated. Analyzing the graph provided us with the optimumvalue.